Overview Of Patients' Knowledge About Tuberculosis At The Sumugung Health Center - Muhammad Iqbal Tawakal; Yasin Wahyurianto; Binti Yunariyah; Roudlotul Jannah (CV. AFDIFAL MAJU BERKAH, 2025)
Tuberculosis (TB) is a contagious infectious disease that remains a global health problem, with varying levels of public knowledge about the disease. Patients' lack of knowledge about the symptoms, spread, and prevention of TB can worsen transmission rates and affect the success of treatment. This study aims to describe the level of knowledge of TB patients at the Sumurgung Community Health Centre and analyze the relationship between their demographic characteristics and their level of knowledge. The method used was a quantitative descriptive study with a cross-sectional approach, involving 60 respondents selected by purposive sampling. The main instrument was a questionnaire based on indicators of knowledge about the definition, symptoms, causes, transmission, and prevention of TB. The data were then analyzed descriptively and cross-tabulated using frequency statistics and percentages. The results showed that around 40% of respondents had a low level of knowledge, with characteristics of being aged 26–45 years, male, and having a junior high school/high school education, which tended to have low knowledge. In conclusion, the level of knowledge of TB patients in this region still needs to be improved through targeted education programs. Efforts are needed to increase public understanding to support more effective control of transmission and successful treatment of TB.